Embracing Literacy Culture in Islamic Education: A Virtual Ethnography Review of the @Publikasiilmiah Account - Muttaqin, Muhammad; Zaimuddin, Zaimuddin; Wahyudi, Muhammad; Arrochman, Ichromsyah; Murtosiah, Siti (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2023)
The Indonesian people's commitment to literacy is being actively promoted through a range of platforms, including forums, groups, activists, and the Ministry of Education and Culture (Kemendikbud), both online and offline. The task is particularly formidable amidst the Covid-19 pandemic, which has significantly impacted several aspects of people's lives, including education, over the past two years. The collective endeavors made by different entities not only aim to increase the level of reading awareness in Indonesian society but also strive to achieve a higher goal, which is to enhance literacy and work consciousness among the Indonesian population, particularly those involved in the academic and educational sphere. The literacy program has grown to include social media as a platform, in response to the growing technology advancements. This appears to enhance the depth and diversity of literacy initiatives, such as the @publikasiilmiah Instagram account, which boasts a following of 69.3 thousand individuals and has shared 15.9 thousand pieces of information. Subsequently, the writer does library research, employing qualitative analytical methodologies and drawing upon the ethnographic theory of cyber-virtual media. The user's text is “Rulli Nasrullah.” By sharing informative content through the @publikasiilmiah account, which reaches a wide online audience, the account demonstrates a high level of expertise in the field of cyber media. This expertise has positive effects on motivation and literacy in activities such as journal writing contests, conferences, and webinars.